Technology of forming modified epoxy composite coatings for the protection of oil and gas complex structures - О. B. Кlymovets, V. P. Kashytskyi*, О. L. Sadova (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2023)
The work defines the adhesive strength of epoxy composite coatings formed by different technological modes, which contain finely dispersed powder of titanium oxide (TiO2) and polyvinyl chloride dissolved in cyclohexanone. The highest values of adhesive strength were obtained for two-layer coatings, in which the lower (adhesive) layer contains chromium (III) oxide powder, and the upper (operational) layer consists of a modified epoxy polymer binder filled with treated titanium (IV) oxide powder. The formation modes of epoxy composite coatings were optimized, for which higher values of adhesive strength were obtained. Higher values of toughness by 40–45 % were obtained for epoxy composites, for which the forming technology included exposure of polyvinyl chloride powder in cyclohexanone with the subsequent introduction of TiO2 powder. This ensures saturation of the filler particles surface with polyvinyl chloride macromolecules, which form additional chemical bonds and perceive dynamic loads. The practical purpose of the developed epoxy composite coating is to protect the constructions, equipment and the oil and gas hardware complex from the influence of hydroabrasive flows during the transportation of oil and petroleum products, which is a complex effect of aggressive substances, water and temperature, which cause the appearance of areas of destruction on the internal surfaces of pipelines and equipment. The difficulty of applying epoxy composite coatings containing prepared finely dispersed titanium (IV) oxide powder is that the powder particles coagulation occurs. The use of cyclohexanone increases the manufacturability of the composition by reducing the ability of powder particles to coagulate.